Interactions between Campylobacters and their bacteriophages - Brathwaite, Kelly Janelle (2015)
Campylobacter jejuni is a leading cause of human bacterial enteritis worldwide. Consumption of contaminated poultry meat is considered a major source of infection. The use of virulent bacteriophages as a form of biocontrol to specifically reduce this pathogen in poultry (phage therapy) is a promising intervention that does not rely on antimicrobials and therefore circumvents the emergence of antibiotic-resistant Campylobacter strains. In order to achieve this, a better understanding of the mechanisms involved in phage-host interactions at the molecular level would assist in the development of the strategy and the selection of bacteriophages. The main objective of this study was to therefore examine such interactions between Campylobacter and its virulent phages. To achieve this, the transcriptional response of C. jejuni to phage infection was investigated, along with the role of a Type II restriction-modification system during phage infection of Campylobacter. These studies were conducted using the highly phage-sensitive Campylobacter strain, C. jejuni PT14, in conjunction with a number of group II and III bacteriophages (Eucampyvirinae).